The Adipokinetic Hormone Receptor Modulates Sexual Behavior, Pheromone Perception and Pheromone Production in a Sex-Specific and Starvation-Dependent Manner in Drosophila melanogaster - Lebreton, Sébastien; Mansourian, Suzan; Bigarreau, Julie; Dekker, Teun (Frontiers in Ecology and Evolution, 2016)
Food availability and nutritional status shape the reproductive activity of many animals. In rodents, hormones such as gonadotropin-releasing hormone (GnRH), restore energy homeostasis not only through regulating e.g. caloric intake and energy housekeeping, but also through modulating sex drive. We investigated whether the insect homologue of the GnRH receptor, the adipokinetic hormone receptor (AKHR) modulates sexual behavior of the fruit fly Drosophila melanogaster depending on nutritional status. We found that AKHR regulates male, but not female sexual behavior in a starvation-dependent manner. Males lacking AKHR showed a severe decrease in their courtship activity when starved, as well as an increase in mating duration when fed. AKHR expression is particularly strong in the subesophageal zone (SEZ, Ito et al. 2014). We found axonal projections from AKHR-expressing neurons to higher brain centers including specific glomeruli in the antennal lobe. Among the glomeruli that received projections were those dedicated to detecting the male specific pheromone cis-vaccenyl acetate (cVA). Accordingly, responses to cVA were dependent on the nutritional status of flies. AKHR was also involved in the regulation of the production of cuticular pheromones, 7,11-heptacosadiene and 7-tricosene. This effect was observed only in females and depended on their feeding state. AKHR has therefore a dual role on both pheromone perception and production. For the first time our study shows an effect of AKHR on insect sexual behavior and physiology. Our results support the hypothesis of a conserved role of the GnRH/AKH pathway on a nutritional state-dependent regulation of reproduction in both vertebrates and invertebrates.